KONSELING INDIVIDUAL TEHADAP PEMILIHAN KARIER SISWA SMAN 1 BATUJAJAR - Desi Kusumah; R. Ika Mustika; Devy Sekar Ayu ningrum (IKIP Siliwangi, 2022)
Career selection is very important for students so that they know where they will continue after graduating from school, therefore there is a need for individual counseling or counseling for the maturity of students' career choices. The technique used in this individual counseling is client cantered, which is to provide guidance so that students can solve the problems they face. Researchers used two students as subjects in implementing individual counseling services withtechniques client centered , because not a few students had problems in the form of difficulties in determining secondary schools. The purpose of this study was to find out the implementation, response and constraints in the implementation of individual counseling usingtechniques client centered for students who have problems in determining careers. This study used a qualitative approach, and the data collection techniques used were observation, interviews and documentation. The results of the study indicate that individual counseling usingtechniques client centered can help determine the secondary school according to their wishes, talents and interests. After attending individual counseling services, students often seek information and ask questions about secondary schools.Keywords: : Career, Client Centered